Penguatan Kapasitas Akademik melalui Workshop Metodologi Research and Development (R&D) bagi Akademisi (Studi Pengabdian pada Program Doktor PAI UIN Syarif Hidayatullah Jakarta) - Rodhiyana, Mu'allimah; Rosyid, Abdul; Asmawi, Moh. (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service (PkM) activity aims to strengthen the academic capacity of lecturers, doctoral students, and academics in Islamic Religious Education (PAI) through a Research and Development (RD) methodology workshop. This activity was motivated by the low conceptual and applicative understanding of PAI academics regarding development research in producing innovative and relevant learning products in the digital era. The implementation method used a participatory approach through an online workshop that included material presentations, interactive discussions, and academic reflections involving participants from across universities. The results of the activity showed an increase in participants' understanding of the characteristics, stages, and implementation of RD research in PAI learning. Participants also developed initial skills in designing RD research oriented towards the development of PAI media, modules, and learning models. The online workshop proved effective as an academic PkM model that is adaptive to digital transformation and contributes to strengthening research culture and improving the quality of PAI scientific publications.